TRANSFORMATION OF TRADITION OF BARONG NGELAWANG IN TOURISM AREA OF UBUD, GIANYAR, BALI - Sukerna, I Nyoman; Wirawan, A.A Bagus; Kumbara, A.A. Ngurah Anom; Sukerta, Pande Made (E-Journal of Cultural Studies, 2016)
Globalization carries new values and touches all aspects of life, one of which is  the tradition of barong ngelawang. This present study is intended to discuss the pattern of transformation, ideology and meaning of the tradition of barong ngelawang in the tourism area of Ubud, Gianyar, Bali. The study views the tradition of barong ngelawang as a text of which the context, why and how it is performed should be understood. The theory of social practice, the theory of ideology, and the theory of semiotics were used to analyze the data. The descriptive and interpretative method was employed. The result of the study shows that the tradition of barong ngelawang in Ubud was transformed from being a scared performance into a secular performance, and from a secular performance into a sacred performance. The transformation also took place in the space dimension. The ideologies which led to the activity of barong ngelawang were the religious ideology and solidarity ideology. The secular activity of barong ngelawang was dominated by the ideology of creativity and the economic ideology. From the ideological context, the meanings which could be revealed from the activity of barong ngelawang were the religious meaning and artistic meaning. From the superstructure context, the meanings that could be revealed were the social stratification meaning, the job description meaning, and the educational meaning. From the infrastructure context, the meaning which could be revealed was the economic meaning.